Kontribusi Kader Posyandu dalam Intervensi Stunting: Kajian Literatur Tahun 2023–2025 - Aulia, Fita Oktaviani; Dewi Purnamawati (Jurnal Ilmu Medis Indonesia, 2025)
Purpose: This research aims to examine how empowering Posyandu cadres through training in health status monitoring and nutrition counseling can contribute to reducing stunting rates among toddlers in Indonesia. Methodology/Approach: The study adopts a systematic literature review method, analyzing 35 relevant sources published between 2023 and 2025. The literature includes indexed journal articles, community service reports, government policy documents, theses, and dissertations. Databases such as Google Scholar, PubMed, DOAJ, SINTA, and Garuda Ristekbrin were used with keyword combinations like "Posyandu cadres," "cadre empowerment," "stunting prevention," and "toddler nutrition." Inclusion criteria were based on methodological quality, relevance to cadre empowerment, and contributions to the theme of stunting prevention. Thematic analysis was employed to extract key findings and identify trends and best practices. Results/Findings: The findings reveal that structured training programs, community-based education, and support from local health authorities significantly enhance Posyandu cadres’ abilities to monitor child growth and counsel families on balanced nutrition. Multisector collaboration and use of digital health tools also improve intervention efficiency. Empowered cadres play a crucial role in early detection of growth problems, improving family compliance with nutritional guidelines, and sustaining long-term stunting reduction efforts. Conclusions: Empowering Posyandu cadres is essential for effective stunting prevention. Investment in training, incentives, digital tools, and food-based local interventions should be prioritized. Limitations: The study only includes literature in Indonesian and English from the last three years and does not perform a quantitative meta-analysis. Contribution: This review offers a scientific basis for formulating community-based policies and strategies to strengthen Posyandu cadres’ capacity as frontline health workers.